2016
DOI: 10.9781/ijimai.2016.4112
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Emotional State of a User Using a Webcam

Abstract: -In online learning is more difficult for teachers identify to see how individual students behave. Student's emotions like self-esteem, motivation, commitment, and others that are believed to be determinant in student's performance can not be ignored, as they are known (affective states and also learning styles) to greatly influence student's learning. The ability of the computer to evaluate the emotional state of the user is getting bigger attention. By evaluating the emotional state, there is an attempt to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Notwithstanding the limitations of emotion recognition described above, topical hardware developments on regular computer equipment [23] would now enable emotion recognition at a larger scale [7]. A typical example would be the use of common webcams for emotion recognition from facial expressions [7,52]. It has been suggested that e-learning applications can benefit from such emotion recognition devices for more natural interactions [71] because they collect data of learners continuously and unobtrusively [7,8].…”
Section: Emotion Recognition In E-learningmentioning
confidence: 99%
“…Notwithstanding the limitations of emotion recognition described above, topical hardware developments on regular computer equipment [23] would now enable emotion recognition at a larger scale [7]. A typical example would be the use of common webcams for emotion recognition from facial expressions [7,52]. It has been suggested that e-learning applications can benefit from such emotion recognition devices for more natural interactions [71] because they collect data of learners continuously and unobtrusively [7,8].…”
Section: Emotion Recognition In E-learningmentioning
confidence: 99%
“…Real-time detection of the face with many other objects in the background is not a simple problem. There are situations in which it is not possible to capture the face of an object due to face rotation of more than about 30°, or to a change in the lighting, other factors which might inhibit facial appearance, such as, beards, glasses [18] [19]. The second phase is extraction, and this is determined by certain specifications and requires particular features to detect an object.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, real-time emotion recognition studies have been encountered in e-learning. For instance, Magdin et al [14] have designed software, which evaluates the emotional state of the user using a webcam. The system works in real time using neural networks.…”
Section: Introductionmentioning
confidence: 99%